Inhomogeneous molecular ring around the B[e] supergiant LHA 120-S 73. - Kraus, M. (2016)
Context. B[e] supergiants are evolved massive stars, enshrouded in a dense wind and surrounded by a molecular and dusty disk. Themechanisms that drive phases of enhanced mass loss and mass ejections, responsible for the shaping of the circumstellar material ofthese objects, are still unclear.Aims. We aim to improve our knowledge on the structure and dynamics of the circumstellar disk of the Large Magellanic Cloud B[e]supergiant LHA 120-S 73.Methods. High-resolution optical and near-infrared spectroscopic data were obtained over a period of 16 and 7 years, respectively.The spectra cover the diagnostic emission lines from [Ca ii] and [O i], as well as the CO bands. These features trace the disk atdifferent distances from the star. We analyzed the kinematics of the individual emission regions by modeling their emission profiles.A low-resolution mid-infrared spectrum was obtained as well, which provides information on the composition of the dusty disk.Results. All diagnostic emission features display double-peaked line profiles, which we interpret as due to Keplerian rotation. We findthat the profile of each forbidden line contains contributions from two spatially clearly distinct rings. In total, we find that LHA 120-S 73 is surrounded by at least four individual rings of material with alternating densities (or by a disk with strongly non-monotonicradial density distribution). Moreover, we find that the molecular ring must have gaps or at least strong density inhomogeneities,or in other words, a clumpy structure. The optical spectra additionally display a broad emission feature at 6160?6180 Å, which weinterpret as molecular emission from TiO. The mid-infrared spectrum displays features of oxygen- and carbon-rich grain species,which indicates a long-lived, stable dusty disk.We cannot confirm the previously reported high value for the stellar rotation velocity. He i λ 5876 is the only clearly detectable pureatmospheric absorption line in our data. Its line profile is strongly variable in both width and shape and resembles of those seen innon-radially pulsating stars. A proper determination of the real underlying stellar rotation velocity is hence not possible.Conclusions. The existence of multiple stable and clumpy rings of alternating density recalls ring structures around planets. Althoughthere is currently insufficient observational evidence, it is tempting to propose a scenario with one (or more) minor bodies or planetsrevolving around LHA 120-S 73 and stabilizing the ring system, in analogy to the shepherd moons in planetary systems.